2022
DOI: 10.3389/fbioe.2022.968482
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-engineered repair material for pelvic floor dysfunction

Abstract: Pelvic floor dysfunction (PFD) is a highly prevalent urogynecology disorder affecting many women worldwide, with symptoms including pelvic organ prolapse (POP), stress urinary incontinence (SUI), fecal incontinence, and overactive bladder syndrome (OAB). At present, the clinical treatments of PFD are still conservative and symptom-based, including non-surgical treatment and surgery. Surgical repair is an effective and durable treatment for PFD, and synthetic and biological materials can be used to enforce or r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…It is the ideal body structure, and an intact set of round ligaments can be of great help in treatment of uterine prolapse. Although synthetic and biomaterials can be used in the treatment of pelvic floor dysfunction disorders, such as uterine prolapse, possibly they can lead to a series of serious complications such as polypropylene meshes that can lead to mesh erosion, exposure, pain and inflammation, while biopatches have poor mechanical properties and degrade rapidly, leading to poor anatomical reduction, which in turn limits their clinical use [ 22 ]. Hernia surgeons should be proactive in protecting the round ligament of uterus.…”
Section: Discussionmentioning
confidence: 99%
“…It is the ideal body structure, and an intact set of round ligaments can be of great help in treatment of uterine prolapse. Although synthetic and biomaterials can be used in the treatment of pelvic floor dysfunction disorders, such as uterine prolapse, possibly they can lead to a series of serious complications such as polypropylene meshes that can lead to mesh erosion, exposure, pain and inflammation, while biopatches have poor mechanical properties and degrade rapidly, leading to poor anatomical reduction, which in turn limits their clinical use [ 22 ]. Hernia surgeons should be proactive in protecting the round ligament of uterus.…”
Section: Discussionmentioning
confidence: 99%
“…The development of tissue engineering and regenerative medicine provides new possibilities for refractory degenerative diseases ( Ma et al, 2021 ). Considering the strong correlation between PFD and connective tissue injury, mesenchymal stem cells (MSCs) have great potential as seed cells ( Lin et al, 2022 ). Previous studies have confirmed its safety and possible effectiveness ( Mukherjee et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Their physical properties (e.g., porosity, mesh weight, and mechanical properties) and manufacturing processes are important regulatory bases for cell adhesion, tissue repair, and regeneration. 10 Preparation methods such as freeze drying, gas forming, solvent casting-particle leaching and electrostatic spinning have been used for the preparation of porous scaffolds with collagen, alginate, silk fibroin, and poly(lactic acid-co-glycolic acid) stent materials. [11][12][13] However, these methods are unable to control the microstructure of scaffolds.…”
Section: Introductionmentioning
confidence: 99%